2010
DOI: 10.1243/09544054jem1959
|View full text |Cite
|
Sign up to set email alerts
|

Study on mechanical, micro-, and macrostructural characteristics of dissimilar friction stir welding of AA6061-T6 and AA7075-T6

Abstract: This research presents the effect of welding speed on dissimilar joints of AA7075-T6 and AA6061-T6 alloys. The weld quality was evaluated through observations of the macrostructure. The mechanical properties of the welds, including the ultimate strength, the percentage of elongation, and the microhardness variations, were determined for different welding speeds. Also the effect of the positions of the two alloys on the mechanical properties was investigated. In addition, during the friction stir welding (FSW) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…The recrystallisation caused by the temperature rising during FSW can readily destroy the hardened state and significantly weaken the mechanical properties. In addition, precipitation hardening is one of the strengthening mechanisms for heat-treatable AA6061 [29,30], and grain size also plays an important role according to the Hall-Petch relationship [31]. For AA6061, the main strengthening phase is the needle-shaped β″ phase.…”
Section: Uniaxial Tensile Propertiesmentioning
confidence: 99%
“…The recrystallisation caused by the temperature rising during FSW can readily destroy the hardened state and significantly weaken the mechanical properties. In addition, precipitation hardening is one of the strengthening mechanisms for heat-treatable AA6061 [29,30], and grain size also plays an important role according to the Hall-Petch relationship [31]. For AA6061, the main strengthening phase is the needle-shaped β″ phase.…”
Section: Uniaxial Tensile Propertiesmentioning
confidence: 99%
“…Since recent publications do not give definitive direction as to the optimal weld configuration (i.e., the placement of the alloy on the retreating or advancing side), the examined joints were produced in two configurations. Some researchers [10,14,28,29] reported that when the weaker alloy is placed on the retreating side, the produced weld becomes weaker compared to the opposite configuration. However, according to other investigations [12,13,30], the more efficient mixing of materials and better properties can be achieved with the softer alloy on the advancing side and the harder alloy on the retreating side.…”
Section: Effect Of Alloy Configurationmentioning
confidence: 99%
“…Peening [14] is a cold working technique which replaces the tensile residual stresses produced by the welding process at the weld region with favorable compressive residual stresses, which effectively introduce a substantial initiation period in the fatigue life of the welded components [15,16]. In this study, a new postweld treatment method, friction stir processing (FSP) [17][18][19], is proposed to extend fatigue life by improving the weld bead shape and the metal structure at the weld zone. For that, first of all, an adequate pin shape and process conditions for FSP were developed through experimentation.…”
Section: Introductionmentioning
confidence: 99%